General self-efficacy in the Norwegian population: Differences and similarities between sociodemographic groups. Issue 7 (November 2019) - Bonsaksen, Tore; Lerdal, Anners; Heir, Trond; Ekeberg, Øivind; Skogstad, Laila; Grimholt, Tine K.; Schou-Bredal, Inger
Aims: General self-efficacy (GSE) refers to optimistic self-beliefs of being able to perform and control behaviors, and is linked with various physical and mental health outcomes. Measures of self-efficacy are commonly used in health research with clinical populations, but are less explored in relationship to sociodemographic characteristics in general populations. This study investigated GSE in relation to sociodemographic characteristics in the general population in Norway. Methods: As part of a larger national survey, the GSE scale was administered to a general population sample, and 1787 out of 4961 eligible participants (response rate 36%) completed the scale. Group comparisons were conducted using independent t -tests and one-way analyses of variance. Linear regression analysis was used to examine factors independently associated with GSE. Results: GSE was lower for older compared to younger participants ( p < 0.001). It was higher for men compared to women ( p < 0.001), higher for those with higher levels of education compared to those with lower levels ( p < 0.001) and higher for those in work compared to their counterparts ( p < 0.001). Controlling for all variables, male gender and employment were independently associated with higher GSE. Age moderated the associations between gender and employment on one hand, and GSE on the other. The association between being male and having higher GSE was more pronounced in younger age, as was the association between being employed and having higher GSE. Conclusions: Male gender and being employed were related to higher GSE among persons in the general population in Norway, and these associations were stronger among persons of younger age. The findings are considered fairly representative for the Norwegian population.